KETERAMPILAN DASAR GURU (TENAGA DIDIK) DALAM PROSES PEMBELAJARAN - Akmal Fadhiilah; Ali Ahmad; Arjun Rampal; Rio Navy Saputra; Muhammad Imam; Septi Fitri Meilana (STKIP Subang, 2025)
Basic teaching skills are essential competencies that every educator must possess to create effective, efficient, and meaningful learning experiences. This material discusses eight fundamental teaching skills: opening and closing lessons, explaining, questioning, reinforcing, varying teaching styles, guiding small group discussions, managing the classroom, and teaching individuals or small groups. Mastery of these skills enables teachers to establish a conducive learning environment and encourage active student participation. In practice, these skills must be continuously developed through training, self-reflection, and evaluation. This material aims to provide both theoretical foundations and practical guidance for educators to enhance their professionalism and the quality of the learning process in the classroom.